HASIL BELAJAR MATERI KOMPUTER DAN JARINGAN DASAR: SEBUAH EFEK DARI MINAT BELAJAR DAN FASILITAS BELAJAR: Learning Outcomes of Basic Computer and Network Materials: An Effect of Learning Interest and Learning Facilities - Neti Neti; Paulina Cindi; Kordelinda Wati; Wita Afrianty; Evita Rizeki (Lembaga Pengembangan Kinerja Dosen, 2022)
The main objective of this study is to identify the factors that have the greatest impact on the overall quality of education received by students. Interest in learning and the availability of educational facilities are two characteristics that are considered to affect the results. Multiple Linear Regression was used to understand this finding. Information was collected using questionnaires and test results, and then given to students, with 26 of them representing the entire population of grade 10 SMK Al-Falah. The findings collected include the fact that 1) there is an influence of interest in learning on learning achievement / learning outcomes 2) Learning facilities do not have a substantial impact on the results of the learning process. 3) The level of interest in learning and the facilities available for learning both have a major influence on the results of the learning process. The most significant component in improving basic computer and network learning outcomes is maintaining interest in the material being studied.